UPAYA MENINGKATKAN CRITICAL THINKING SKILL DALAM PEMBELAJARAN PPKN DENGAN MODEL RADEC PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Tarigan, Maria; Rifatunnisa, Rifatunnisa; Taofik, Taofik; Muji, Nidya Chandra Muji (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Critical thinking skills possessed by grade V students at SDN Kalisari 01 Pagi are still relatively low, based on observations, problems were found related to the low critical thinking skills of students in Civics learning. After being given a pretest according to critical thinking indicators, there were only 3 students who were complete. If this condition is allowed, the objectives of Civics learning will not be achieved and students in the 21st century will not be able to compete, because they do not have qualified skills. Therefore, researchers propose a solution by applying the RADEC learning model which aims at critical thinking skills, especially in Civics subjects. In this study using the classroom action research method from the Kemmis & McTaggart model, through various stages, namely planning, implementing action and observation, and reflection. The subjects of this study were 27 students in class V, with data collection techniques such as interviews, documentation, observations, and final tests. Then, the data analysis technique uses quantitative analysis to examine the results of the evaluation test and qualitative analysis will describe the research process using observation results. During cycle I there was an increase with a percentage of 37% of students who were complete with an average of 62.5. This research was continued until cycle II and obtained an average score of 75.8 with 63% of students having a complete score.